Evaluation of mono- and dipeptides as organocatalysts for enantioselective aldol reaction - Yolacan, Cigdem; Mavis, Murat Emrah; Aydogan, Feray (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Catalytic activities of (3S)-1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid (THIQA)-based mono- and dipeptides and their L-proline analogs in asymmetric aldol reaction were investigated. THIQA-based dipeptides showed better enantioselectivity than proline analogs, whereas proline-based dipeptides gave higher yield in the aldol reaction of cyclohexanone with several aldehydes in dichloromethane at -10 degrees C in the presence of benzoic acid. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Aldol reaction; Tetrahydroisoquinoline-3-carboxylic acid; Proline; Organocatalysis; Asymmetric synthesis; SMALL ORGANIC-MOLECULES; THIOUREA BIFUNCTIONAL CATALYSTS; PROLINE-BASED ORGANOCATALYST; ASYMMETRIC MICHAEL ADDITION; AMIDE; ALDEHYDES; WATER; DERIVATIVES; INHIBITORS; Chemistry